2013
DOI: 10.1074/mcp.m113.027383
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Insulin/Insulin-like Growth Factor-1 Signaling and Dietary Restriction Inhibit Translation but Preserve Muscle Mass in Caenorhabditis elegans

Abstract: Reduced signaling through the C. elegans insulin/insulin-like growth factor-1-like tyrosine kinase receptor daf-2 and dietary restriction via bacterial dilution are two well-characterized lifespan-extending interventions that operate in parallel or through (partially) independent mechanisms. Using accurate mass and time tag LC-MS/MS quantitative proteomics, we detected that the abundance of a large number of ribosomal subunits is decreased in response to dietary restriction, as well as in the daf-2(e1370) insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
128
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(145 citation statements)
references
References 160 publications
(218 reference statements)
15
128
2
Order By: Relevance
“…Although some evidence points toward BCAAs as a metabolic signature of long life in C. elegans insulin receptor mutants (31,32), other studies have causally linked BCAAs to the development of insulin resistance, diabetes (33), and neuropathologies (34). Interestingly, BCAAs, leucine in particular, are potent activators of the target of rapamycin (TOR) kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Although some evidence points toward BCAAs as a metabolic signature of long life in C. elegans insulin receptor mutants (31,32), other studies have causally linked BCAAs to the development of insulin resistance, diabetes (33), and neuropathologies (34). Interestingly, BCAAs, leucine in particular, are potent activators of the target of rapamycin (TOR) kinase.…”
Section: Discussionmentioning
confidence: 99%
“…For example, DR can be achieved by diluting the bacteria in a liquid medium. This intervention, which extends the lifespan and decreases animal size, is partially dependent on both daf-16, a key transcription factor of the insulin-like signaling pathway, and aak-2, the catalytic subunit of AMP-activated protein kinase (AMPK) (7,8). In a different DR model, a mutation in the eat-2 gene decreases the rate of pharyngeal contractions, limiting the animals' feeding rate.…”
mentioning
confidence: 99%
“…With the dawn of the omics era, transcriptomic (McElwee et al, 2003;Murphy et al, 2003;McElwee et al, 2004;Halaschek-Wiener et al, 2005), proteomic (Dong et al, 2007;Jones et al, 2010;Depuydt et al, 2013Depuydt et al, , 2014Stout et al, 2013;Walther et al, 2015) and metabolomic (Fuchs et al, 2010) studies showed that IIS mutants undergo massive changes in gene expression and shifts in metabolic networks. DAF-16 targets were also determined by analysing DNA binding sites of this transcription factor with DamID and ChIP (Oh et al, 2006;Schuster et al, 2010).…”
Section: The Foxo/daf-16 Lifespan Programmentioning
confidence: 99%
“…Quantitative proteomics data showed a clear decrease in ribosomal subunits and translation factors in daf-2 mutants suggesting a decrease in protein synthesis rates in these worms (Depuydt et al, 2013;Stout et al, 2013). Active insulin and IGF pathways are known to support anabolic growth.…”
Section: Damage Clearance and Protein Turnovermentioning
confidence: 99%